Transformative learning: writing narrative comedy as creative resistance. Issue 6 (2nd November 2018) - Cake, Susan
ABSTRACT: This paper examines a self-directed, transformative, learning journey triggered by the writer-researcher's experiences of change management which led to widespread redundancies within the vocational education sector in Queensland, Australia. The creative-practice led research focussed on writing narrative comedy screenplays, titled Fighting Fit . Critical reflection was embedded in the research methodology. Reflective writing was documented in a reflection journal and triangulated against external feedback to improve screenplay drafts. Critical feedback on scripts provoked a cycle of inquiry into the lived experiences which inspired the screenplays and highlighted concerns about diminished professional agency and alienation in the workplace. These concerns were then reframed within a humorous perspective by parodying discourses surrounding organisational change management. In doing so, the creative practice-led research enabled the writer-researcher to examine her professional disquiet in response to workplace changes, crystallise values in conflict with neoliberal approaches to education and performed a kind of creative resistance to the corporatisation of vocational education. Moreover, critical reflection embedded in creative writing processes shifted the writer-researcher's perspective towards an increased sense of agency and openness to change; arguably, a desirable outcome for practitioners operating within increasingly precarious employment situations.